Fizzics : the science of bubbles, droplets, and foams - Young, F. Ronald (Johns Hopkins University Press, 2011)
"We've all spent summers past blowing bubbles in the backyard. But the humble bubble (and its opposite, the droplet) are fascinating cornerstones of the world around us. This book, breathtaking in its scope, describes for a general reader (no math, no physics, no equations) the compelling behavior of these seemingly simple objects. Young reveals the secrets of successful springboard diving, whether knuckle cracking gives you arthritis, and why dolphins can't go faster. The realm of droplets allows our author to showcase why the sky is blue, how atom smashers work, and the rich source of science that is the kitchen faucet. He explores collections of bubbles--foams--and discusses the early years of Margaret Thatcher, how a metallic foam might save the planet, and the never-ending quest for the perfect pint. Then, by looking at soap films, he tells you how to construct a soapy computer, why coffee rings form, and exactly how a detergent gets dishes clean. Beyond these basics, Young shows how humans put bubbles to use, whether in technology (refining minerals, making concrete harder, or generating light) or in medicine (cleaning wounds with hydrogen peroxide, the debilitating process of the bends, and how pharmaceutical bubbles can make ultrasounds far clearer). This is more than a book that explains science. It is a love letter written to sing the praises of the bubble, and can be read by the bright middle schooler on upward"--